2017
DOI: 10.2196/jmir.7583
|View full text |Cite
|
Sign up to set email alerts
|

Improving Employee Well-Being and Effectiveness: Systematic Review and Meta-Analysis of Web-Based Psychological Interventions Delivered in the Workplace

Abstract: BackgroundStress, depression, and anxiety among working populations can result in reduced work performance and increased absenteeism. Although there is evidence that these common mental health problems are preventable and treatable in the workplace, uptake of psychological treatments among the working population is low. One way to address this may be the delivery of occupational digital mental health interventions. While there is convincing evidence for delivering digital psychological interventions within a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
235
5
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(289 citation statements)
references
References 83 publications
12
235
5
12
Order By: Relevance
“…This finding may indicate that when participants focused more on the scheme's self-monitoring and feedback aspects, this was associated with less of a decline in PA and is in line with the results of the study's mediation analyses which found planning and habit formation are important mediators [5]. Previous research also shows that self-regulation techniques and self-monitoring are useful strategies for PA behaviour change [34,[59][60][61][62][63] and one previous systematic review of web-based interventions also highlights that web-based self-monitoring is a potentially effective technique [64]. Redeeming a higher proportion of earned points for rewards was associated with slightly higher PA levels at six months.…”
Section: Intervention Engagement and Physical Activitysupporting
confidence: 83%
“…This finding may indicate that when participants focused more on the scheme's self-monitoring and feedback aspects, this was associated with less of a decline in PA and is in line with the results of the study's mediation analyses which found planning and habit formation are important mediators [5]. Previous research also shows that self-regulation techniques and self-monitoring are useful strategies for PA behaviour change [34,[59][60][61][62][63] and one previous systematic review of web-based interventions also highlights that web-based self-monitoring is a potentially effective technique [64]. Redeeming a higher proportion of earned points for rewards was associated with slightly higher PA levels at six months.…”
Section: Intervention Engagement and Physical Activitysupporting
confidence: 83%
“…In the current study, the program arguably promoted mental health by cultivating mindfulness; however, more global effects on depression, and anxiety may require the direct address of work-related risk factors. Similarly, online occupational mental health interventions appear to be most effective when they are multi-modal, for example combining online content with text-message reminders [67]. This may be particularly true with online workplace mindfulness programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the model likely has a wider application. Both the workplace and the Internet have increasingly become a vehicle for reaching working adults with primary prevention and health promotion messages across a wide variety of topics (Carolan, Harris, & Cavanagh, ; Gosling & Mason, ; Rogers, Lemmen, Kramer, Mann, & Chopra, ). These topics include mental health and related risks, stress management, diet and nutrition, and disease management.…”
Section: Methodsmentioning
confidence: 99%